Civil society funding by OECD-DAC governments: no more politics as usual?. Issue 6 (17th August 2020) - Verbrugge, Boris; Huyse, Huib
ABSTRACT: While the amounts of ODA funding that OECD-DAC countries are channelling to and through civil society organisations (CSOs) are at an all-time high, there are growing concerns over the future of government-to-CSO funding. This analysis of the funding situation in five European countries reveals that despite the resilience of CSO funding, there have been important changes in how this funding is managed and allocated. Moreover, the sense of unease about CSO funding is also a reaction to broader political trends, such as the increased emphasis on aid effectiveness, and widespread concerns about closing civic space.